The Mediating Role of Brand Image in Celebrity Endorser and E-WOM Effects on Gen Z's MS GLOW Purchase Decisions in Semarang - Syafaq, Shandya Aissy; Firdaus, Firdaus; Abdullah, Zailani (International Journal of Management Science and Information Technology, 2026)
This study examines the mediating role of Brand Image in the relationship between Celebrity Endorsers, Electronic Word of Mouth (E-WOM), and purchasing decisions among Generation Z consumers of MS GLOW skincare products in Semarang, Indonesia. Employing a quantitative approach with twenty measurement indicators across four constructs and using an accidental sampling technique, the study investigates how different communication sources influence Gen Z consumers’ perceptions and purchase behavior in the local skincare market. The findings reveal that Celebrity Endorsers neither significantly shape Brand Image nor directly influence purchasing decisions, indicating that celebrity-based persuasion has limited effectiveness for this consumer segment. In contrast, E-WOM exerts a positive and significant effect on both Brand Image and purchasing decisions, underscoring the importance of peer-generated information in building trust and guiding consumer choice. Brand Image is also found to significantly influence purchasing decisions and partially mediate the relationship between E-WOM and purchase behavior, while no mediating effect is observed in the relationship between Celebrity Endorsers and purchasing decisions. These results empirically demonstrate that, within the context of Gen Z skincare consumption in Semarang, peer communication plays a more decisive role than celebrity endorsement. Theoretically, this study refines branding and consumer behavior literature by clarifying the differentiated influence pathways of E-WOM and endorsement cues. Practically, the findings suggest that skincare brands targeting Gen Z should prioritize peer-based digital engagement strategies over celebrity-driven promotion.